Improving subspace learning for facial expression recognition using person dependent and geometrically enriched training sets - Bolis, Dimitris; Tefas, Anastasios; Pitas, Ioannis K.; Maronidis, Anastasios (My University, 2011)
In this paper, the robustness of appearance-based subspace learning techniques in geometrical transformations of the images is explored. A number of such techniques are presented and tested using four facial expression databases. A strong correlation between the recognition accuracy and the image registration error has been observed. Although it is common-knowledge that appearance-based methods are sensitive to image registration errors, there is no systematic experiment reported in the literature. As a result of these experiments, the training set enrichment with translated, scaled and rotated images is proposed for confronting the low robustness of these techniques in facial expression recognition. Moreover, person dependent training is proven to be much more accurate for facial expression recognition than generic learning.
Keywords: Facial expression recognition; Appearance based techniques; Subspace learning methods